A new result on Branciari metric space using (α, γ)-contractive mappings - Patil Jayashree; Hardan Basel; Hamoud Ahmed A.; Bachhav Amol; Emadifar Homan (Topological Algebra and its Applications, 2022)
In this work, a new common fixed point result by generalized contractive functions fulfilling the type of admissibility condition in a Hausdorff Branciari metric space with the support of C-functions, was obtained.